Design of a set of nonlinear control systems of the arc PVD ionplasma installation - Kyrkopulo, Kateryna; Tonkonogyi, Vladimir; Stopakevych, Oleksii; Stopakevych, Andrii (Eastern-European Journal of Enterprise Technologies, 2018)
Control systems over the set of technological processes of the installation for ion-plasma application of coatings on metal cutting tools are developed. The purpose of the development is the need to improve the quality and durability of manufactured tools by maintaining more accurate technological parameters of the installation. The result of our research is the developed new nonlinear models of control systems over all stages of operation. At the stage of ionic cleaning, a temperature rise in tool is maintained in line with the set linear program by enabling and disabling the arc discharge. Control system provides for a deviation from the program by ±4.5 K, which is 4 times less than the standard value. At the stage of applying a coating on the tool, the temperature is precisely stabilized in a vacuum chamber by a continuous change in voltage at the substrate, as well as pressure in it by a change in the flow rate of nitrogen into the chamber. Under the action of maximal disturbances, a deviation in pressure, 0.037 Pa, and in temperature, 0.45 K, is ensured. At the stage of cooling, a decrease in temperature is achieved in line with the program by changing the feed of nitrogen into the chamber. Under the action of maximal disturbances, a maximum cooling rate of 0.22 K/s is ensured, which is also better than the standard value. Thus, the application of the developed control systems allowed us to considerably improve tool resistance compared to the installations that are used at present. It is important that the developed control systems are easy to implement and make it possible to ensure high quality of the obtained tools.